Problematika Pembelajaran Bahasa Arab Kelas III di Sekolah Dasar Islam Plus Al-Ittiba’ Juwiring Klaten Tahun Ajaran 2022/2023 - Muhammad Fahmi (Thulabuna: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to describe the Arabic language learning process, the problems encountered, the solutions implemented to overcome these problems, and the curriculum targets at Sekolah Dasar Islam Plus Al-Ittiba’ Juwiring Klaten. This research uses a descriptive qualitative approach. The data collection techniques used are observation, interviews, and documentation. The data analysis method involves collecting data, reducing data, presenting data, and drawing conclusions. The results of this study show that the implementation of Arabic language learning at Sekolah Dasar Islam Plus Al-Ittiba’ Juwiring Klaten begins with the teacher reading and explaining the material, after which students are given assignments using the Arabic textbook published by Pustaka Sofwa. The problems faced in Arabic language learning include: the Arabic language teacher is not a graduate of an Arabic language education program; students are not enthusiastic about Arabic learning due to monotonous teaching methods; the time allocated is insufficient; and the curriculum used is outdated. The solutions proposed are: ideally, the Arabic language teacher should be a graduate of an Arabic language education program; the teacher should provide more student motivation and use more varied methods; the time allocated for Arabic learning should be increased; and the curriculum should be updated to the latest version. The goal of the curriculum is to shape students into intelligent, devout, and well-mannered Muslims.